Management of BUMDesma Mahalona Raya in Enhancing Community Welfare in Mahalona Village, East Luwu Regency - Panca Rakhmat; Risma Niswaty; Herman H; Ismail (International Journal Of Public Policy and Bureaucracy, 2025)
This study aims to examine the governance of BUMDesma Mahalona Raya in promoting community welfare, focusing on key supporting and inhibiting factors in its implementation. Employing a qualitative approach, data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings reveal strong management professionalism reflected in transparent recruitment, adherence to organizational statutes, and routine SOP evaluations. Governance practices also show a high degree of openness and accountability, with financial disclosures presented in village forums and participatory meetings. Community participation is active across decision-making, program implementation, and partnerships with third parties. The prioritization of local resources is evident through product marketing, skills training, and inclusive economic activities. However, sustainability remains a challenge due to limited green initiatives, narrow business diversification, and incomplete financial transparency. Supporting factors include consistent government support, strong community involvement, and geographic advantage, while barriers include unstable leadership, limited capital, and restricted access to technology. This research contributes to improving BUMDesma governance policy by highlighting the importance of leadership stability, inclusive financial practices, and institutional continuity to ensure long-term welfare impacts in rural areas.